Communication in the neonatal ICU for Spanish speaking parents: a qualitative interview study - Emily Batton; Samantha Hurst; Carlos Ramos; Leslie Catalan; Michele Freeman; Krishelle Marc-Aurele (BMC, 2023)
Abstract Background In the neonatal intensive care unit (NICU), health outcome disparities exist between patients with limited English proficiency (LEP) and those proficient in English. Our objective was to investigate the communication experience of parents with LEP in the NICU to learn how to mitigate such health disparities. Methods A certified bilingual provider conducted seventeen interviews of parents who identified Spanish as their preferred language and whose newborn was admitted to the NICU for ≥ 1 week. Interviews were conducted August 2020 - December 2021. Conventional content analysis utilizing an inductive open coding process was performed. Results The experiences of Spanish speaking parents with LEP in the NICU can be characterized by 3 main themes: 1) Information accessibility 2) Perspectives about interpreters and 3) Emotional consequences. Conclusions Our findings can inform neonatal quality initiatives to facilitate timely and good communication for NICU families with LEP.